A national audit on the utilization and documentation of dabigatran checklist for patients initiated on dabigatran - Devaraj, Navin Kumar; George, Doris; Mohamad, Noraini; Rahmat, Shakirin Shaik; Mohamed, Sahimi (Malaysian Medical Association, 2019)
Background: Direct oral anticoagulants (DOACs) especially dabigatran, have gain popularity for their efficacy, fixed dosing and favourable safety profile. A dabigatran prescribing checklist has been prepared by the Ministry of Health, Malaysia (MOH) to ensure rational and safe prescribing of dabigatran. This study therefore aimed to audit the utilization and documentation of this checklist and use of dabigatran in the government healthcare facilities. Methods: This is a nationwide retrospective audit on the documentation of Dabigatran Prescribing and Dispensing Checklist for a period of two years from January 2013 till December 2014. Data from these Dabigatran Checklists (indication, dose, duration, renal function and adverse drug reactions encountered) were extracted by the pharmacist at MOH healthcare facilities. Results: A total of 52 out of 56 (92.9%) of MOH facilities complied to usage of checklist at their centres involving a total of 582 patients of which 569 (97.7%) patients were initiated on dabigatran for the approved indications. The recommended dose of dabigatran was used correctly in 501 (99.6%) of patients. Reason for switching to DOACs use was only documented in 76.7% (131/171) of patients. The most common reason for switching from warfarin was poor INR control (n=39), history of bleeding/overwarfarinisation (n=22) and unable to attend regular INR clinic (n=21). There were 75 cases of adverse events reported. The most common adverse event reported were abdominal discomfort (n=10) followed by gum bleeding (n=9) and dizziness (n=5). Conclusions: Compliance to the dabigatran check list was high with 70% of patients prescribed the appropriate dosing.